EFEKTIVITAS TUGAS NAZHIR DALAM PENGELOLAAN TANAH WAKAF DI KOTA BENGKULU - Anohib, Anohib (Institut Agama Islam Bengkulu, 2017)
The purpose of this study is to determine the effectiveness of wakaf land management by nazhir and to know the nazhir constraints in the management of wakaf land in the city of Bengkulu. To solve the problem deeply and thoroughly, researchers used a qualitative approach with primary data collection techniques through interviews with nazhir. From the results of the study found that the management of wakaf land by nazhir not effective, because the number is still small, while the potential that should be used a lot. of the 21 mosques studied, only 6 mosques that have had management Percentage 28.57% (6 of 21). Wakaf land management by nazhir also has not been effective in terms of management field, because there is no management other than education field, whereas management of wakaf land can also be managed in the field of economy and health in accordance with the potential land wakaf.Keywords: Effectiveness, Nazhir Task, Wakaf Land Management.Â